Effect of Cardiac Function on Cognition and Brain Structural Changes in Dementia - Oh, Ji Eun; Shin, Jong Wook; Sohn, Eun-Hee; Jung, Jin Ok; Jeong, Seong Hae; Song, Hee Jung; Kim, Jae-Moon; Lee, Ae Young (Journal of clinical neurology (Seoul, Korea), 2012)
Cardiovascular risk factors are considered to also be risk factors for dementia. Recent studies have shown that the prevalence of cognitive dysfunction is high in patients with cardiac diseases. However, few studies have investigated the influence of cardiac function on cognition and brain structural changes in dementia. The aims of this study were to determine the relationship between cardiac and cognitive function, and to characterize any structural changes in the brain that could be caused by cardiac function in patients with dementia. Dementia patients (n=93) were recruited prospectively with checking for the presence of vascular risk factors such as hypertension. Cognitive function was measured by the Mini-Mental State Examination, modified Mini-Mental State test, and Korean version of the Dementia Rating Scale. Brain magnetic resonance imaging was conducted to evaluate the cerebral white-matter changes (WMC), ventricular dilation, and cortical and hippocampal atrophy. Cardiac function was evaluated using two-dimensional echocardiography. We divided the patients into two groups according to the presence (+) or absence (-) of WMC. In the entire cohort, the size of the left atrium (LA) was positively correlated with the degree of WMC, irrespective of age (p<0.05). The LA was larger in the WMC (+) group (n=42) than in the WMC (-) group. General cognitive function was significantly lower in the WMC (+) group than in the WMC (-) group. Subjects with an enlarged LA tended to exhibit lower cognitive function and more-severe cerebral WMC. Cardiac dysfunction represented by LA enlargement could be related to cognitive decline and WMC of the brain resulting from impairment of the cerebral hemodynamic process in dementia.